THE INFLUENCE OF EMOTIONAL INTELLIGENCE AND WORK ENVIRONMENT ON JOB SATISFACTION IN STATE VOCATIONAL SCHOOL TEACHERS IN THE EAST JAKARTA REGION - Iqmaulia, Khilda; Karyaningsih, RR Ponco Dewi; Munawaroh (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2022)
This study aims to analyze the effect of Emotional Intelligence and Work Environment on Job Satisfaction in State Vocational High School Teachers in the East Jakarta Region. This research was conducted for six months from October 2021 to March 2022. The method used in this study was a survey or questionnaire distribution using a Likert scale. The sample used in this study obtained 227 teacher respondents from 13 State Vocational Schools in East Jakarta who were accredited A. Based on the research conducted, it was found that there was a positive influence between Emotional Intelligence and Job Satisfaction and there was also a positive influence between Work Environment and Job Satisfaction.